2013
DOI: 10.1063/1.4793526
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition of platinum within nanopores on silicon: Drastic acceleration originating from surface-induced phase transition

Abstract: An electrochemical reaction within nanopores is remarkably decelerated once a diffusion-limited condition is reached due to the difficulty in supply of reactants from the bulk. Here, we report a powerful method of overcoming this problem for electrochemical deposition of platinum within nanopores formed on silicon. We made the pore wall surface of the silicon electrode hydrophobic by covering it with organic molecules and adopted platinum complex ions with sufficiently large sizes. Such ions, which are only we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 50 publications
1
45
2
Order By: Relevance
“…When the ion concentration in the bulk is gradually increased, at a threshold the deposition behavior exhibits a sudden change, leading to drastic acceleration of the electrochemical deposition. 26 Using our statistical-mechanical theory for confined molecular liquids, we have shown that this change originates from a surfaceinduced phase transition: The space within a nanopore is abruptly filled with the second phase in which the ion concentration is orders of magnitude higher than that in the bulk. 26 The threshold concentration is lowered when the ionic size is made larger (that is, [PtCl 4 ] 2− with d − = 0.60 nm (d − is the anion diameter) is replaced by [PtBr 4 ] 2− with d − = 0.70 nm; the latter is more hydrophobic).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…When the ion concentration in the bulk is gradually increased, at a threshold the deposition behavior exhibits a sudden change, leading to drastic acceleration of the electrochemical deposition. 26 Using our statistical-mechanical theory for confined molecular liquids, we have shown that this change originates from a surfaceinduced phase transition: The space within a nanopore is abruptly filled with the second phase in which the ion concentration is orders of magnitude higher than that in the bulk. 26 The threshold concentration is lowered when the ionic size is made larger (that is, [PtCl 4 ] 2− with d − = 0.60 nm (d − is the anion diameter) is replaced by [PtBr 4 ] 2− with d − = 0.70 nm; the latter is more hydrophobic).…”
Section: Introductionmentioning
confidence: 97%
“…26 Using our statistical-mechanical theory for confined molecular liquids, we have shown that this change originates from a surfaceinduced phase transition: The space within a nanopore is abruptly filled with the second phase in which the ion concentration is orders of magnitude higher than that in the bulk. 26 The threshold concentration is lowered when the ionic size is made larger (that is, [PtCl 4 ] 2− with d − = 0.60 nm (d − is the anion diameter) is replaced by [PtBr 4 ] 2− with d − = 0.70 nm; the latter is more hydrophobic). 25,26 When the pore wall surface is made hydrophilic, by contrast, there is no such striking behavior observed: It seems that the enrichment of the ionic concentration near the hydrophilic surface does not occur and the electrochemical deposition within nanopores does not proceed irrespective of the ionic concentration in the bulk.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Such a difference has been evaluated both experimentally and theoretically. [26][27][28] In aqueous solutions, it has been shown that weakly hydrated solutes are excluded from the bulk to a hydrophobic surface. The similar behavior, i.e., hydrophilic solutes are excluded to hydrophilic surface in hydrophobic solvent, has been reported, e.g., ethanol is concentrated on the surface of silica in cyclohexane.…”
Section: Discussionmentioning
confidence: 99%